2021
DOI: 10.1007/s00248-021-01865-x
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Microbiome Diversity Varies Along a Landscape-Scale Moisture Gradient

Abstract: Microorganisms live in close association with metazoan hosts and form symbiotic microbiotas that modulate host biology. Although the function of host-associated microbiomes may change with composition, hosts within a population can exhibit high turnover in microbiome composition among individuals. However, environmental drivers of this variation are inadequately described. Here, we test the hypothesis that this diversity among the microbiomes of Aedes albopictus (a mosquito disease vector) is associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…We next validated our isolation and cryopreservation approach using microbiota derived from water collected from a naturally occurring larval habitat in the field. As expected, the bacterial community present in this habitat was comprised of a substantially higher diversity of ~1,000 unique taxa, although these taxa were dominated by members of the same phyla (Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria) detected in laboratory rearing pans and commonly detected in field-collected mosquitoes (5,51,52,(56)(57)(58)(59)(60)(61)(62)(84)(85)(86)(87)(88)(89)(90)(91)(97)(98)(99)(100)(101)(102). Recovery of field-derived taxa in experimental microcosms generated using cryopreserved material from the same habitat was also overall much lower than what we observed in microcosms generated using cryopreserved stocks of lab-derived microbiota, although the taxa lost or significantly reduced in microcosms generated using cryopreserved material were consistent with those lost or significantly reduced in microcosms generated using fresh material-strongly suggesting that the observed shifts in alpha and beta diversity in microcosms were not the result of cryopreservation but rather the inability of many field-derived taxa to thrive under conventional mosquito rearing conditions in the laboratory.…”
Section: Discussionsupporting
confidence: 61%
“…We next validated our isolation and cryopreservation approach using microbiota derived from water collected from a naturally occurring larval habitat in the field. As expected, the bacterial community present in this habitat was comprised of a substantially higher diversity of ~1,000 unique taxa, although these taxa were dominated by members of the same phyla (Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria) detected in laboratory rearing pans and commonly detected in field-collected mosquitoes (5,51,52,(56)(57)(58)(59)(60)(61)(62)(84)(85)(86)(87)(88)(89)(90)(91)(97)(98)(99)(100)(101)(102). Recovery of field-derived taxa in experimental microcosms generated using cryopreserved material from the same habitat was also overall much lower than what we observed in microcosms generated using cryopreserved stocks of lab-derived microbiota, although the taxa lost or significantly reduced in microcosms generated using cryopreserved material were consistent with those lost or significantly reduced in microcosms generated using fresh material-strongly suggesting that the observed shifts in alpha and beta diversity in microcosms were not the result of cryopreservation but rather the inability of many field-derived taxa to thrive under conventional mosquito rearing conditions in the laboratory.…”
Section: Discussionsupporting
confidence: 61%
“…We next validated our isolation and cryopreservation approach using microbiota derived from water collected from a naturally occurring larval habitat in the field. As expected, the bacterial community present in this habitat was comprised of a substantially higher diversity of ~1,000 unique taxa, although these taxa were dominated by members of the same phyla (Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria) detected in laboratory rearing pans and commonly detected in field-collected mosquitoes [2,10,11,[15][16][17][18][19][42][43][44][45][46][47][48][49][60][61][62][63][64][65]. Recovery of field-derived taxa in experimental microcosms generated using cryopreserved material from the same habitat was also overall much lower than what we observed in microcosms generated using cryopreserved stocks of lab-derived microbiota, although the taxa lost or significantly reduced in microcosms generated using cryopreserved material were consistent with those lost or significantly reduced in microcosms generated using fresh material-strongly suggesting that the observed shifts in alpha and beta diversity in microcosms were not the result of cryopreservation but rather the inability of many field-derived taxa to thrive under conventional mosquito rearing conditions in the laboratory.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 66%
“…However, the immense diversity and variability of the PLOS NEGLECTED TROPICAL DISEASES microbiota within and between different populations of mosquitoes in the laboratory and field have made studying mosquito-microbe interactions-and identifying bacteria that reduce the vectorial capacity of mosquitoes-a formidable challenge [1]. As in other animals, numerous factors have the potential to shape variation in mosquito microbiota and therefore variation in mosquito phenotypes, including the microbiota present in the aquatic environment in which larvae develop, environmental conditions (e.g., diet, temperature), and host genetics [2,3,10,11,[15][16][17][18][19][42][43][44][45][46][47][48][49][50]. However, while experiments with mosquitoes are commonly conducted using genetically identical individuals under highly controlled environmental conditions, tools to standardize the microbiota present in the larval rearing environment are comparatively limited [3,13,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…This association is driven by 10 ASVs from different taxonomic groups that correlate strongly and/or significantly with aspects of precipitation (Figure S17 ). An effect of precipitation‐related variables has also been found in mosquitoes, where the gut microbiome changes along a landscape–moisture gradient (Medeiros et al, 2021 ), and exposure to altered humidity has been shown to change the microbiome in mice (Yin et al, 2022 ). However, our association study cannot discern whether symbiont abundance is shaped directly by humidity irrespective of the host or indirectly by the host as a response to humidity.…”
Section: Discussionmentioning
confidence: 94%